MAKNA DAN PERAN KOSMOLOGI DALAM PEMBENTUKAN POLA PERKAMPUNGAN TRADISIONAL SASAK - Dewi, Ni Ketut Agusinta (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 2 (2016): Agustus 2016, 2016)
Traditional settlement evolves through a long socio-cultural process. It commences with system of thoughts which then lead to the establishment of behavioural norms and codes. When the entire process is disseminated and handed down from generation to generation, it constructs a distinctive identity specific to particular communal entity. As part of a diverse society of the Nusantara (a name after the Indonesian Archipelago), Sasak Communities demonstrate a unique characteristic by their methods in embracing nature into their spatial organization. Socio-spatial forms of these societies are clear representations of their long spatial traditions, unique blend of native belief sistem of Sasak Boda , Hinduism, flourished in their neighbouring Island of Bali, and Islamic (or Islam Watu Telu ) influence thrived in Lombok. Similar to the Balinese-Hinduism principles, Sasak Communities crucially take micro and macro-cosmos into consideration in organizing the layout and orientation of their settlement. This directs an arrangement of a well-lined and symmetrical spatial pattern. Founded by these conditions, this study seeks to explore the determining factors that guide the unique spatial structure of Sasak settlements. It summarizes that cosmological principles, the astronomical lining of the sun and the geographical direction of the mountain (Rinjani) are the three determinants, fundamental to the spatial organization of the Sasak Communities. Keywords: cosmology; spatial formation of a traditional settlement; Sasak community Abstrak Hunian dan permukiman tradisional lahir dari sebuah proses sosial budaya yang panjang. Proses tersebut merupakan gagasan pola pikir lalu berkembang menjadi norma-norma perilaku dari masyarakatnya. Ketika proses tersebut diwariskan turun-temurun dari generasi ke generasi, hingga akhirnya membentuk sebuah identitas. Sebagai bagian dari masyarakat tradisional Nusantara, Suku Sasak merupakan salah satu suku bangsa yang memiliki kekhasan di dalam membaca alam dan mengatur permukimannya. Perwujudan budaya huniannya sangat bertalian erat dengan norma-norma tradisi, percampuran budaya antara sistem kepercayaan Sasak Boda , arsitektur Hindu di Bali dan arsitektur Islam (Islam Watu Telu). Masyarakat tradisional Sasak di Lombok masih berorientasi terhadap kepercayaan makro dan mikro kosmos dalam mengatur tata letak dan arah hadap rumah. Ini membuat masyarakat tradisional ini memiliki pola ruang permukiman yang teratur dan simetris. Berdasarkan fenomena tersebut, studi ini bertujuan untuk memaparkan peran kosmologi pada pembentukan pola permukiman di dusun-dusun tradisional Sasak. Hasil studi menunjukkan bahwa konsep ruang makro masyarakat tradisional Sasak terbentuk berdasarkan konsep filosofi kosmologi dari lintasan matahari dan kesakralan gunung Rinjani.
Keywords: kosmologi; pola perkampungan tradisional; Suku Sasak